Kontestasi Politik antara Kesultanan Deli dan Serdang di Sumatera Timur, 1800-1865 - Syauqii, Fachri; Yasmin, Nabila; Naldo, Jufri (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This study aims to determine the political contestation between the Deli and Serdang Sultanates and to determine the impact of the contestation. This study uses the historical method with four steps, namely: heuristics, verification, interpretation, and historiography. The sources of data used in this study include primary and secondary sources. Primary sources are agreement texts and interviews. While secondary sources are obtained through several books, theses, and journals related to the two sultanates. The analysis used is deductive, namely drawing conclusions from the general to the specific, in which the political contestation in the Deli and Serdang Sultanates, so as to obtain information on how the political contestation between the two.